2017
DOI: 10.18632/oncotarget.22795
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective phase II study of first-line modified FOLFIRINOX for unresectable advanced pancreatic cancer

Abstract: BackgroundFOLFIRINOX (FX) has been reported as an effective treatment for unresectable advanced pancreatic cancer. However, FX is associated with a high incidence of adverse events (AEs). A previous phase II study in Japan showed high incidences of hematological AEs, including febrile neutropenia (22.2%). A modified FX regimen (mFX) may decrease the rates of AEs and be more effective than FX by improving the treatment compliance.AimsTo assess the safety and efficacy of first-line mFX for unresectable advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…Only 70 studies were eligible upon abstract screening. After full-text screening, only 11 studies remained, and they were included in the final analysis 20 – 30 .
Figure 1 Flow chart for study search (PRISMA diagram).
…”
Section: Resultsmentioning
confidence: 99%
“…Only 70 studies were eligible upon abstract screening. After full-text screening, only 11 studies remained, and they were included in the final analysis 20 – 30 .
Figure 1 Flow chart for study search (PRISMA diagram).
…”
Section: Resultsmentioning
confidence: 99%
“…Regarding neutropenia, 77.8% of patients experienced severe neutropenia in a Japanese phase II study of sFOLFIRINOX for chemotherapy-naïve MPC, which is similar to our study’s findings[ 22 ]. In addition, most studies conducted in Asian countries reported severe neutropenia in > 65% of patients[ 23 - 26 ], which was more frequent than that in reports from western countries (11.0%-45.7%)[ 7 , 27 - 29 ]. These results suggest that Asians may be prone to severe FOLFIRINOX-related neutropenia, and dose adjustment is an option that should be considered when treating patients belonging to the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, dose escalation was not performed even if the adverse events disappeared. The criteria for dose reduction was chosen according a Japanese phase II study on modified FOLFIRINOX [ 6 ]. Briefly, treatment was delayed when one or more of the following adverse events occurred: grade 3–4 neutropenia or thrombocytopenia, febrile neutropenia, total bilirubin >3.0 mg/dL, aspartate transaminase and alanine transaminase >150 U/L, creatinine >1.5 mg/dL, grade 3–4 peripheral neuropathy, and grade 3–4 diarrhea.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the incidence of toxicities associated with FOLFIRINOX, the chemotherapy regimen has been modified by omission the bolus injection of 5-FU and/or reducing the dose of irinotecan without reducing the clinical response [ 5 , 6 , 7 , 8 , 9 ]. Modification of the FOLFIRINOX regimen (oxaliplatin 85 mg/m 2 , irinotecan 150 mg/m 2 , 5-FU infusion 2400 mg/m 2 over 46 h, no bolus 5-FU) reduces the incidence of grade 3–4 neutropenia to 47.8% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%